1992
DOI: 10.1111/j.1365-2559.1992.tb00939.x
|View full text |Cite
|
Sign up to set email alerts
|

The nature of breast dense core granules: chromogranin reactivity

Abstract: Ultrastructural immunoreactivity for chromogranin with the LK2H10 antibody was examined in nine cases of breast carcinoma and one example of normal resting breast. These tissues were selected for study on the basis of argyrophilia or LK2H10 immunostaining by light microscopy. In two cases, positive reactivity with the chromogranin antibody was seen in breast neuroendocrine-like dense core granules. In a further six cases chromogranin reactivity was not seen in similar granules that showed the neuroendocrine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Immunoelectron microscopy studies demonstrated the presence of ChA-negative dense core granules in breast carcinomas reactive for ChA in light microscopy (32), and ChA-negative dense core granules were found on the cell apex of solid papillary NE carcinomas (33). The authors presumed that these granules could be positive for other types of Chs.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoelectron microscopy studies demonstrated the presence of ChA-negative dense core granules in breast carcinomas reactive for ChA in light microscopy (32), and ChA-negative dense core granules were found on the cell apex of solid papillary NE carcinomas (33). The authors presumed that these granules could be positive for other types of Chs.…”
Section: Discussionmentioning
confidence: 99%
“…The chromogranins form a family of proteins that includes at least three members: types A, B, and C [41]. Endocrine breast cancers can synthesize either type A or type B; tumours producing only the latter tend to occur in postmenopausal women and pursue an indolent clinical course [2,46]. Both types of chromogranin contribute to the matrix of dense core granules [2,6,37,46] and probably give rise to the granules' argyrophilia [2,3,6,37,41].…”
Section: What Specialized Studies Provide Convincing Evidence Of Neurmentioning
confidence: 99%
“…The latter arise from indigenous endocrine cells and form repetitive histological patterns that do not overlap with those of other types of carcinoma except in unusual examples. Endocrine tumours of the breast probably do not arise from pre-existing endocrine cells, since investigators have observed them only rarely and then only in small numbers [2,3,34,44]. Furthermore, mammary endocrine tumours do not grow with unique histological characteristics; instead the neoplasms often resemble other types of breast cancer and virtually never duplicate the appearances of intestinal or pulmonary carcinoid tumours.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the presence of small and large electron dense granules support this contention, although we acknowledge that such granules as those in case 1 do not always indicate neuroendocrine diVerentiation. 13 The diVerential diagnosis of predominantly clear and spindle cell DCIS includes both apocrine and neuroendocrine DCIS, myoepithelial DCIS, and presumably intraductal variants of glycogen and lipid rich carcinomas, as well as fixation artefact. 2 As distinct entities, apocrine and neuroendocrine DCIS are not uncommon, but their occurrence as a mixed or combined subtype of DCIS with an unusual dimorphic appearance appears to be a rare event.…”
Section: Discussionmentioning
confidence: 99%